2010
DOI: 10.1007/s00435-010-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

The catecholaminergic nerve plexus of Holothuroidea

Abstract: Catecholamines have been extensively reported to be present in most animal groups, including members of Echinodermata. In this study, we investigated the presence and distribution of catecholaminergic nerves in two members of the Holothuroidea, Holothuria glaberrima (Selenka, 1867) (Aspidochirotida, Holothuroidea) and Holothuria mexicana (Ludwig, 1875) (Aspidochirotida, Holothuroidea), by using induced fluorescence for catecholamines on tissue sections and immunohistochemistry with an antibody that recognizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…However, some of the differences observed in the enteric nervous system of the three species could also be due to variations associated with the level of the intestinal tissue that was studied and not necessarily species differences. Such differences have been well documented in H. glaberrima where, for example an intestinal catecholaminergic plexus is observed in the esophagus and descending small intestine but is not found in other intestinal regions (Diaz-Balzac et al 2010b). In this respect, it is important to highlight that the posterior (large) intestine of H. mexicana was studied, but for the other two species the sections were obtained at mid-body level, thus it is not clear if the intestinal tissue at that level corresponds (anatomically or functionally) to a more small intestine (nutrient absorptive function) or large intestine (feces compaction function) type.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, some of the differences observed in the enteric nervous system of the three species could also be due to variations associated with the level of the intestinal tissue that was studied and not necessarily species differences. Such differences have been well documented in H. glaberrima where, for example an intestinal catecholaminergic plexus is observed in the esophagus and descending small intestine but is not found in other intestinal regions (Diaz-Balzac et al 2010b). In this respect, it is important to highlight that the posterior (large) intestine of H. mexicana was studied, but for the other two species the sections were obtained at mid-body level, thus it is not clear if the intestinal tissue at that level corresponds (anatomically or functionally) to a more small intestine (nutrient absorptive function) or large intestine (feces compaction function) type.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, anti-nurr1 is the first marker that appears to preferentially identify cells of the hyponeural component over those of the ectoneural component, contrary to anti-galanin, which preferentially identify cells and fibers of the ectoneural component (Diaz-Miranda et al 1996). This is particularly surprising in view of the fact that in vertebrates, Nurr1 function has been associated with the catecholaminergic neurotransmitter system (Zetterstrom et al 1997), but previous studies from our group have shown that the holothurian catecholaminergic system is present within the ectoneural component of the radial nerve cord (Diaz-Balzac et al 2010b). Finally, most of the cells immunoreactive to anti-PH3 and anti-pax6 were found outside of the radial nerve cord, suggesting that they correspond to a peripheral nervous system component and that most of the fibers identified by these antibodies within the radial nerve cord itself might correspond to afferent fibers originating from the somas localized in peripheral regions, such as the podial nerve or enteric nervous system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Smaller subpopulations of neurons have also been characterized by using previously described nervous system markers, particularly neurotransmitters or their synthesizing enzymes or neuropeptides. Thus, the gabaergic and catecholaminergic nervous system components of echinoderms have been described [ 9 , 10 ] as have been many neurons, neuroendocrine cells and fibers that express neuropeptides. This is the case for SALMFamide [ 11 , 12 ], GFSKLYFamide [ 13 ], galanin [ 14 ], and FMRFamide [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, almost all knowledge of the nervous system of echinoderms was based on classical histology carried out early during the last century and, more recently, on electron microscopy studies (e.g., Bouland et al., 1982; Cavey, 2006; Flammang & Jangoux, 1992; Hyman, 1955; McKenzie, 1987; Pentreath & Cobb, 1972; VandenSpiegel et al., 1995). With the development of new neural markers, neuronal populations expressing different neurotransmitters, such as catecholamines and neuropeptides, have been identified, contributing to a more comprehensive view of the echinoderm nervous system (Díaz‐Balzac, Abreu‐Arbelo, & García‐Arrarás, 2010; Díaz‐Balzac & García‐Arrarás, 2018; Díaz‐Balzac, Mejías, Jiménez, & García‐Arrarás, 2010; Díaz‐Balzac et al., 2007, 2014; Díaz‐Miranda, Blanco, & Garcia‐Arraras, 1995; Hoekstra, Moroz, & Heyland, 2012; Inoue, Tamori, & Motokawa, 2002).…”
Section: Introductionmentioning
confidence: 99%